Effect of BTCLS Training on Emergency Department Clinicians' Competencies in Cardiac Arrest Management: A Single-Group Pretest–Posttest Study at Pongtiku General Hospital - Rante, Anshar; Rasyid, Djusmadi; Dg Salimung, Hardianto; M, Warda (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
ntroduction: Cardiac arrest refers to a critical condition in which the heart abruptly ceases to pump blood effectively, leading to an interruption of blood flow throughout the body. This disruption prevents vital organs, including the brain and heart, from receiving the necessary oxygen and nutrients. Without immediate intervention, cardiac arrest can result in fatality or irreversible brain damage within minutes. The Emergency Department is pivotal in managing cardiac arrest cases. As the first line of healthcare response, it is imperative for medical personnel to engage in ongoing training and education to enhance the quality of emergency care, particularly in scenarios involving cardiac arrest Methods: This study employed a single-group pretest-posttest design involving 24 clinicians from the emergency department of Rumah Sakit Umum (RSU) Pongtiku. Data collection utilized validated instruments, including a 25-item multiple-choice knowledge assessment (Cronbach’s ? = 0.87) and a 10-item psychomotor skill checklist (inter-rater reliability = 0.89). The normality of the data was assessed using the Shapiro-Wilk test. Given that the data did not follow a normal distribution, the Wilcoxon signed-rank test was used for analysis. Results: The results of the analysis using the Wilcoxon Signed Rank Test indicate that all respondents experienced an increase in knowledge scores after being given the educational intervention, with a value of Z = -4.288 and a significance value (Asymp. Sig. 2-tailed) of 0.000 (p < 0.05). This shows that there is a significant difference between pretest and posttest knowledge scores. Therefore, the educational intervention provided is effective in increasing respondents' knowledge.Based on the results of the Wilcoxon Signed-Rank Test analysis, a Z value of -4.046 was obtained, with a significance value (Asymp. Sig. 2-tailed) of 0.000 (p < 0.05). This result indicates that there is a significant difference in skill scores before and after the educational intervention. A total of 21 respondents experienced an increase in their skills, while 3 respondents maintained the same score. Therefore, the educational intervention provided was effective in improving the skills of the respondents. Conclusion: BTCLS training for emergency department nurses significantly increases knowledge scores and standardized skills in the short term. These results support the sustainability of the program and highlight the need for curriculum improvement. Further research is necessary to evaluate retention and its impact on clinical indicators.